Part Two of the Themed Issue on Reimagining Research Methods Coursework for the Preparation of Scholar-Practitioners - Sarah A. Capello; Maxwell Yurkofsky; Edwin Nii Bonney (Impacting Education, 2023)
In this second installment of the themed issue on redesigning research methods coursework for CPED-inspired EdD programs, EdD faculty and students share empirical research, conceptual insights, and practitioner-oriented coursework and activities to contribute to the conversation on research methods training and skill development for scholar-practitioners.